THE ITALIAN EXPERIENCE IN PRECAST CONSTRUCTION IN THE SECOND HALF OF THE 20TH CENTURY: SYSTEMS FOR INDUSTRIAL BUILDINGS - Enrico Dassori; Salvatore Polverino; Clara Vite (Tema)

(untitled)
The developments in concrete prefabrication techniques from the second half of the 20th century, particularly in Italy, have established these methods as a dominant force in the construction of industrial buildings. This period offers a valuable opportunity to explore the industrialisation of the construction sector. The roots of this transformation can be traced back to the 1920s, when a highly rational approach to building design and produc¬tion processes began to take hold in industrial construction. This rationality persisted into the post-World War II era, where technological advancements in materials enabled the creation of innovative and daring structures for industrial purposes. The industrial boom further fueled the demand for new buildings to be constructed rapidly, ensuring swift production capabilities. This article aims to provide an overview of the key precast reinforced concrete construction systems that formed the backbone of industrial construction in the post-war period. During this time, industrial construction fostered experimentation and the development of cutting-edge techniques, achieving significant results across various fields of application. The article offers a taxonomy of the main systems used during the period under review, with a particular focus on structural systems, ranging from those partially cast in situ to fully industrialised systems, as well as on building envelope elements. The goal is to provide a comprehensive understanding of the critical role of precast systems in Italy’s industrialisation.